The addition of capnography to standard monitoring reduces hypoxemic events during gastrointestinal endoscopic sedation: a systematic review and meta-analysis - Kim SH; Park M; Lee J; Kim EJ; Choi YS (Dove Medical Press, 2018)
Seung Hyun Kim,1 Minsu Park,2 Jinae Lee,2 Eungjin Kim,1 Yong Seon Choi3 1Department of Anesthesiology and Pain Medicine, Severance Hospital, Yonsei University College of Medicine, Seoul, Korea; 2Biostatistics Collaboration Unit, Yonsei University College of Medicine, Seoul, Korea; 3Department of Anesthesiology and Pain Medicine, Severance Hospital, Anesthesia and Pain Research Institute, Yonsei University College of Medicine, Seoul, Korea Background: The use of capnography monitoring devices has been shown to lower the rates of hypoxemia via early detection of respiratory depression, and facilitate more accurate titration of sedatives during procedures. The aim of the current meta-analysis was to compare the incidence of hypoxemia associated with standard monitoring alone during gastrointestinal endoscopy to that associated with standard monitoring with the addition of capnography.Methods: The MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials scientific databases were searched to identify relevant studies. We performed a meta-analysis of randomized controlled trials undertaken up to January 2018 that met our predefined inclusion criteria. The study outcome measures were incidence of hypoxemia, severe hypoxemia, apnea, the use of assisted ventilation, the use of supplemental oxygen, and change in vital signs.Results: We included nine trials assessing a total of 3,088 patients who underwent gastrointestinal procedural sedation. Meta-analysis of study outcome revealed that capnography significantly reduced the incidence of hypoxemia (odds ratio 0.61, 95% CI 0.49–0.77) and severe hypoxemia (odds ratio 0.53, 95% CI 0.35–0.81). However, there were no significant differences in other outcomes including incidence of apnea, assisted ventilation, supplemental oxygen, and changes in vital signs. Early procedure termination and patient satisfaction-related outcomes did not differ significantly in the capnography group and the standard monitoring group.Conclusion: This study indicates that capnography monitoring is an important addition with regard to the detection of hypoxemia during gastrointestinal procedural sedation, and should be considered in routine monitoring during gastrointestinal endoscopy. Keywords: endoscopy, additional monitoring, hypoxemia, apnea